Analysing Difference of Accounting Policies Kantor Pelabuhan Laut BP Batam Before and After Status Badan Layanan Umum (BLU) - Victoriana Beatric (Politeknik Negeri Batam, 2014)
This final assignment describe about accounting policies in Kantor Pelabuhan Laut BP Batam which that office is one of unit services in BP Batam. BP Batam has great scope so that in making financing report will be very important. Therefore, researcher wants review difference accounting policies of Kantor Pelabuhan Laut BP Batam before and after status BLU. Methods of data analysis used are descriptive method which researcher describes detailly accounting policies in Kantor Pelabuhan Laut BP Batam. Based on result of research, have known that office has some equations and differences accounting policies of Kantor Pelabuhan Laut BP Batam between before and after status BLU